Estudo de bactérias acidofílicas redutoras de sulfato com potencialidade no tratamento de drenagem ácida de mina - Licona, Frecia Maribel Mamani (2019)
The environmental impact caused by mining affects ecosystems, especially the impacts from acid mine drainage (DAM), which end up affecting surface and groundwater, causing pollution and destruction of ecosystems. DAM is a difficult waste to treat, as it has a high sulfate content, very low pH and significant concentrations of heavy metals. Therefore, the treatment of AMD is a biotechnological challenge. However, there are microorganisms capable of metabolizing sulfate. Sulfate-reducing bacteria (BRS) are widely studied for bioremediation, as they are able to grow in acidic environments, generating alkalinity removing sulfate and precipitating heavy metals present in DAM. In this perspective, the objective of this study was to obtain information about the native BRS existing in the sedimentary basin of the uranium mine operated by the Brazilian Nuclear Industries (INB) in the city of Caldas - MG, focusing on acidophilic BRS that play an important role in the applications. As a viable alternative to reduce the sulfate of this type of effluent and precipitate recoverable metals, in the present study BRS enrichments were made under different conditions in two carbon sources (lactate and acetate) and different pH values ​​( 2,3,4 and 5), the analyzes performed by physicochemical monitoring of sulfate removal and sulfide production were optimal for pH 3,4 and 5 and to know the biodiversity present in the enrichment, a sequencing analysis was performed. 16S rDNA gene reporting 496 genera grouped into 25 phyla, highlighting the presence of 7 BRS for lactate enrichment and 5 BRS for acetate enrichments, concluding with the possibility of characterizing the native BRS existing in the uranium mine sedimentary basin despite the acidic conditions and the presence of heavy metals, which supports the possible use in effluents with this type of characteristics.